2020
DOI: 10.38042/biost.2020.29.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis of some species in Brassicaceae family with ISSR markers

Abstract: Brassicaceae is one of the biggest family which have thousands of species all around the world. In order to use wild mustard in a breeding process, their genetic kinship levels must be defined. Inter simple sequence repeats (ISSRs) are one of the common markers to evaluate genetic diversity. Here, 28 mustard genotypes representing four taxa, 17 of Brassica juncea, 2 of B. nigra, 2 of B. rapa, and 7 of B. arvensis, were investigated with seven ISSR primers. Totally, 160 bands were scored out of which 88.75% sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The analysis clearly grouped wild grown rose hip into bigger fruited ones, sweeter ones or those with a higher content of polyphenolic compounds (Figure 1). Previous studies also indicated large diversity among ecotypes in wild and cultivated plants by using PCA analysis [76][77][78][79][80][81][82].…”
Section: Principal Compenent Analysis (Pca)mentioning
confidence: 99%
“…The analysis clearly grouped wild grown rose hip into bigger fruited ones, sweeter ones or those with a higher content of polyphenolic compounds (Figure 1). Previous studies also indicated large diversity among ecotypes in wild and cultivated plants by using PCA analysis [76][77][78][79][80][81][82].…”
Section: Principal Compenent Analysis (Pca)mentioning
confidence: 99%
“…The number of Crambe species that are endangered necessitates a broad level of genetic diversity analysis for safeguarding and preservation of biodiversity, as well as the development of contemporary varieties of Crambe . Information regarding gene pool polymorphism can be obtained from genetic structure analysis of Crambe populations, demonstrating genetic variance within populations (Maraş Vanlıoğlu et al . 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Turkey is well-known for its rich flora and less-known plants, including fruits, which are widespread with a broad geographic distribution [1][2][3].…”
Section: Introductionmentioning
confidence: 99%